The Effectiveness of Cognitive Behavioral Counseling and Cognitive Restructuring Techniques to Increase Self-Confidence and Learning Motivation in Students - Lidya Sriwayuni Kurniati; I Ketut Gading; Putu Ari Dharmayanti; Ni Ketut Suarni (Bisma The Journal of Counseling, 2025)
Self-confidence and learning motivation are essential factors in students’ learning success. Low levels of these factors can hinder learning effectiveness, highlighting the need for appropriate psychological interventions. This study aims to examine the effectiveness of cognitive behavioral counseling using cognitive restructuring techniques in simultaneously improving students’ self-confidence and learning motivation. This study employed a quasi-experimental method with a pretest–posttest control group design. The research subjects were students with low levels of self-confidence and learning motivation. A total of 30 students were purposively selected from Grade VII and VIII based on pretest results. The intervention was conducted through group cognitive behavioral counseling sessions using cognitive restructuring techniques over eight sessions. Pretest and posttest data were collected using self-confidence and learning motivation questionnaires that had been tested and confirmed to be valid in terms of content validity and empirical validity, and reliable with a very high reliability category. Data were analyzed using the MANOVA test with the assistance of SPSS version 21.0. The results indicate that cognitive behavioral counseling using cognitive restructuring techniques is effective in simultaneously enhancing students’ self-confidence and learning motivation. These findings suggest that this approach can be applied as both a preventive and curative intervention by school counselors to support students’ learning readiness and academic success.